THE PRACTICE OF STREET RACING BY WOMEN: MOTIVATIONAL FACTORS OF ADHERENCE IN A SPORT ADVISORY IN THE CITY OF JOINVILLE/SC (Fiep Bulletin - online, 2019)
Nowadays, the pursuit of physical activities is becoming more frequent, the street race is one of them, because it is asport that is easy to adapt and practice and requires few material resources and can run outdoors as in squares and parks. In thisway, this work had as main objective to analyze among the six motivational dimensions being: Stress Control, Health, Sociability,Competivity, Aesthetics and Pleasure, which motivate the practice of street running by women seeking regular physical activity ina race advisory in the city of Joinville / SC. The data collection was performed at the sports consultancy Corra Bem Saúde (CBS)and the sample comprised of 40 women. The protocol used was Balbinotti's Physical Activity Regular Motivation Inventory(IMPRAF 54, 2006), through a statistical treatment we used the single factor ANOVA test to prove the variance between thegroups, critical F values and p value for verification of the difference between motivations and through Excel we used the meanand standard deviation for analysis of motivational factors. It was verified that the dimension that motivates individuals is Health,followed by Pleasure and Sociability dimensions, and the dimensions of Stress Control, Aesthetics and Competitiveness are theleast motivating. It is hoped that this research, through the most prevalent motivational factor found, will help coaches to have amore individualized and in-depth assessment of women's motivation, making them reach their goal more easily.
Keywords: Street race; motivational factors; benefits of running